Ordered‐Assembly Conductive Nanowires Array with Tunable Polymeric Structure for Specific Organic Vapor Detection. Issue 27 (8th May 2019) - Jiang, Xiangyu; Zhang, Xiqi; Wu, Yuchen; Li, Yunqi; Pang, Jinhui; Zhang, Haitao; Jiang, Lei
Abstract: An artificial organic vapor sensor based on a finite number of 1D nanowires arrays can provide a strategy to allow classification and identification of different analytes with high efficiency, but fabricating a 1D nanowires array is challenging. Here, a coaxial Ag/polymer nanowires array is prepared as an organic vapor sensor with specific recognition, using a strategy combining superwettability‐based nanofabrication and polymeric swelling‐induced resistance change. Such organic vapor sensor containing commercial polymers can successfully classify and identify various organic vapors with good separation efficiency. An Ag/polymer nanowires array with synthetic polyethersulfone polymers is also fabricated, through molecular structure modification of the polymers, to distinguish the similar organic vapors of methanol and ethanol. Theoretical simulation results demonstrate introduction of specific molecular interaction between the designed polymers and organic vapors can improve the specific recognition performance of the sensors. Abstract : An ordered‐assembly conductive nanowires array is fabricated based on Ag/polymer composite for specific organic vapor detection. The nanowires array, originated from different commercial polymers, indicates good separation efficiency for various organic vapors. Through molecular structure modification of synthetic polyethersulfone polymers, the prepared conductive nanowires array can distinguish the similar organic vapors of methanol and ethanol.